Chapter 5 Modality of Transcendental Signification in the Paradiso - De Benedictis, Raffaele (Taylor & Francis, 2024)
In the Paradiso, Dante attempts to emphasize the heightened tension between the limits of human language and the need to put into words a content that deals with divine ineffability. It is a content-stuff that is not codified, and Dante is faced with the problem of narrating his experience that is not comprehensible to humans. The author will analyze those multimodal linguistic and non-linguistic strategies Dante utilizes to allow the reader to gain an idea of his ineffable journey in the afterlife precisely through his Florentine vernacular.